MATHEMATICAL MODEL OF AN EDUCATIONAL PROGRAM QUALITY ASSESSMENT - Khimicheva, Hanna; Volivach, Antonina (Proceedings of National Aviation University (archive), 2020)
The purpose of this article is to substantiate the methods, principles and approaches to building a mathematical model for quantitative assessment of the educational program quality functioning, regardless of the subject area and specialty for which it has been developed. Methods: The article analyzes sixty-five educational programs developed in accordance with thirty-five specialties within fourteen subject areas. These programs operate in forty-nine higher education institutions in different regions of Ukraine. An interval scale has been developed, which allowed translating the qualitative characteristics (criteria) of the educational program into quantitative ones. Using the regression analysis method and software product PRIAM (planning, regression and model analysis) a mathematical model has been built, that allows not only to assess the quality of the educational program in more accurate and reliable way, but also to determine the level and duration of its accreditation. Results: to quantify the educational program quality, a mathematical model has been developed and its statistical characteristics have been analyzed. Informativeness, adequacy, accuracy and stability have been determined, and the diagrams of criteria (regressors) mutual influence on the educational program quality have been built. Discussion: a linear regression model based on a qualimetric approach and TQM principles has been proposed. The use of regression analysis methods allowed to identify the criteria (regressors) mutual influence, determine their priority and quantify the educational program quality as a whole. This approach allows to reasonably choose the optimal number of criteria, their mutual influence and priority. This further allows to more reliably and accurately determine the level of educational program accreditation, which is relevant for each higher education institution.